2015
DOI: 10.1097/meg.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

High local recurrence of early-stage hepatocellular carcinoma after percutaneous thermal ablation in routine clinical practice

Abstract: Local recurrence after PTA for early-stage HCC is high in routine clinical practice. Poorly differentiated HCC and pretreatment α-fetoprotein are important, independent predictors of LTP. Further well-designed randomized controlled trials with larger sample sizes using adjuvant therapies in combination with PTA to decrease LTP rates are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 28 publications
2
28
1
Order By: Relevance
“…For HCC of 2 cm or smaller, the 5-year LTP rates were reported to be 10%–15.9% after RFA [11, 17, 24]. In our study, no significant difference was observed between the two groups in the LTP rate: 9.6% in the MWA group and 10.1% in the RFA group.…”
Section: Discussioncontrasting
confidence: 60%
“…For HCC of 2 cm or smaller, the 5-year LTP rates were reported to be 10%–15.9% after RFA [11, 17, 24]. In our study, no significant difference was observed between the two groups in the LTP rate: 9.6% in the MWA group and 10.1% in the RFA group.…”
Section: Discussioncontrasting
confidence: 60%
“…This has since been published as a full-text article. 28 Thus, a total of 10 studies were included in the final meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A number of investigations have confirmed that poor differentiation and microvascular invasion were related to poor outcomes for patients with HCC after liver resection or RFA. [2][3][4] Moreover, cirrhosis is proposed as a risk factor for late HCC recurrence by many investigations. 2 We suggested how many patients had cirrhosis in each group should be clarified in this study.…”
mentioning
confidence: 99%
“…The local recurrence rate of patients with very early stage HCC was 15.9% in Chinnaratha et al's study, which was similar to the current study. 1,3 RFA can be carried out percutaneously, laparoscopically, or as an open surgery. However, some investigators suggested open surgical ablation was superior to percutaneous ablation for patients with liver cancer.…”
mentioning
confidence: 99%